Desarrollo socio productivo de la Cooperativa agrícola 18 de Noviembre del cantón Santa Rosa 2012 - Sánchez Orosco, Esmeralda Elizabeth (2012)
In Ecuador, the agroeconomic situation has been improved, through cooperativism, which arises from groups of people with a common economic interest and around which also the desire for technological knowledge to achieve better returns, with respect to cooperatives Farming.